Change Management in MSMEs: A Systematic Literature Review (SLR) Study of Adaptation and Digital Transformation Strategies - Palerina Tiara Oktapia; Ratu Ayu Andini; Daffa Algifari; Jesika Amanda; Mayola Yosef; Ririn Harini (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Change management is a key element in maintaining organizational continuity amidst technological advancements, globalization, and the complexity of a constantly changing environment. An organization must be able to adapt and implement change to remain competitive and face emerging challenges. The focus of this research is to investigate organizational adaptation and transformation strategies in implementing change management through a review of various previous studies. The methodology chosen for this study is a Systematic Literature Review (SLR) with a descriptive, qualitative approach. Data collection was conducted by searching for scientific articles in the Scopus, Web of Science, ScienceDirect, and Google Scholar databases using relevant keywords related to change management, adaptation strategies, and organizational transformation. The selected articles were screened based on inclusion and exclusion criteria, ensuring their relevance. The findings of this study indicate that organizational adaptation strategies, such as improving human resources, organizational innovation, flexibility in work systems, and strengthening organizational culture, are crucial for successful change management. Furthermore, organizational transformation, particularly digital transformation, appears to improve operational efficiency, service quality, and the effectiveness of decision-making within the organization. This research also identified that transformational leadership and internal organizational readiness are key factors for successful change implementation within organizations. Using the SLR approach, this research is expected to contribute theoretically to the development of studies on organizational change management and serve as a reference source for organizations in formulating adaptive and sustainable change strategies.